1991
DOI: 10.1039/c39910001484
|View full text |Cite
|
Sign up to set email alerts
|

S,S′-diethyl dithiomalonate as ethanol carbanion equivalent in annelation reactions

Abstract: S,S'-Diethyl dithiomalonate 1 undergoes concomitant alkylation reaction and Michael addition with w-iodo-a,P-unsaturated ketones; the dithiomalonate group present in the cyclization products can be easily reduced by Raney nickel to the ethanol level.$ Iodo enone 10 was prepared from 3-(4-methoxyphenyl)propan-l-o1 according to the following scheme:Reagents and conditions: i, Na, NH3(1);S ii, TsCl, pyridine; iii, 0.1 mol dm-3 HC1; iv, NaI, acetone, reflux 0 The following scheme was used to prepare iodo enone 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
93
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 6 publications
3
93
0
Order By: Relevance
“…This phenomenon has been described in several reports and is based on the finding that photoluminescence of conjugated polymers and related polymeric ensembles can be quenched by means of energy and͞or electron transfer to small molecule quenchers (15)(16)(17)22). In previous studies, it was found that one quencher molecule can quench the photoluminescence of up to several hundred polymer repeat units (25)(26)(27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been described in several reports and is based on the finding that photoluminescence of conjugated polymers and related polymeric ensembles can be quenched by means of energy and͞or electron transfer to small molecule quenchers (15)(16)(17)22). In previous studies, it was found that one quencher molecule can quench the photoluminescence of up to several hundred polymer repeat units (25)(26)(27).…”
mentioning
confidence: 99%
“…These assays require specialized equipment and͞or suffer from low fluorescence intensity change as a function of enzyme activity and generally cannot be used to detect phosphorylation of natural, chemically unmodified protein substrates. The use of native substrates is attractive because inhibitor screens may yield novel inhibitors that affect the enzyme docking site, which can be at a site distant from the active site.We sought to enhance sensitivity in the measurement of enzymatic activity by amplifying the fluorescence signal using superquenching (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). This phenomenon has been described in several reports and is based on the finding that photoluminescence of conjugated polymers and related polymeric ensembles can be quenched by means of energy and͞or electron transfer to small molecule quenchers (15)(16)(17)22).…”
mentioning
confidence: 99%
“…Recently, the activity and stability of Mo/H-ZSM-5 were found to be significantly increased by the addition of small amounts of CO or CO2 in the CH4 feed 15) . Furthermore, Fe and Co had promotional effects on the catalytic properties of Mo/ H-ZSM-5 under the conditions of CO or CO2/CH4 resulting in increased methane conversion, greater selectivity for benzene and reduced coke formation 16) .…”
Section: Introductionmentioning
confidence: 99%
“…18 These templates are reported to be capable of directing growth of 1-D PANI nanostructures with diameters smaller than 100 nm. However, a post-synthetic treatment is required to remove these templates from the products to recover nanostructured PANI.…”
mentioning
confidence: 99%